Capacity Utilization of Small Scale Desalination Plant - Lee, Man Djun (unimas, 2017)
This thesis is about development of a model to evaluate capacity utilization (CU) of small scale desalination plants. In particular, this study is in the field of operations research in manufacturing engineering. Literature review proved that work in this area is limited despite appearing as an important research. In this aspect, the current work is fundamental and novel in the domain of desalination operations research. More specifically, this study focuses on the internal factors of small scale desalination machinery and their impacts towards production performance. Based on literature review findings on desalination process and theories related to CU and production functions, a conceptual model is developed. The conceptual model is then translated into a mathematical model by using relevant theories from literature review. The developed model is rebuilt using short term production function with key production variables. The independent variables are: plant operators, capital, R&D, energy and machinery maintenance expenditure. CU of small scale desalination plant is the output and dependent variable for this study. The developed model is tested on a 5m3/day capacity (small scale) desalination plant in Sadong Jaya. The plant is operating eight hours a day and five days a week to provide potable water to support local residents.